Relationship between thermohaline and biochemical patterns in the levantine upper and intermediate water masses, Southeastern Mediterranean Sea (2013–2021) - Ozer, T.; Rahav, E.; Gertman, I.; Sisma-Ventura, G.; Silverman, J.; Herut, B. (Frontiers in Marine Science, 2022)
The relationships between the interannual variations of the Levantine intermediate water (LIW) core properties and the corresponding biochemical variations in the euphotic zone were systematically studied in the Southeastern Mediterranean during 2013–2021 and since 2002 based on a previous study. Salinity and temperature interannual fluctuations in the LIW continue to follow the Adriatic–Ionian Bimodal Oscillating System (BiOS) mechanism, with salinity and temperature peaks in the years 2008–2010, 2014–2015, and 2018–2019 coinciding with periods of anticyclonic circulation of the North Ionian Gyre (NIG). During these anticyclonic periods, the transport of Atlantic Water into the Levant is reduced together with the transport of LIW out of the basin. These interannual fluctuations are superimposed on a long-term warming trend clearly evident from previous studies, showing a maximal temperature in 2018–2019, higher than the previously mentioned temperature peaks by ~0.7°C and ~0.4°C. The enhanced warming in 2018–2019 has caused a decrease in density (sigma) values of the LIW core, which gave way to the shallowest record of this water mass (~110-m depth), bringing it well within the lower photic zone. We suggest that a higher level of nutrients became available, supporting the observed long-term rise of the intergraded chlorophyll a (Chl.a) (0.89 mg m−2 year−1), with a maximum recorded during 2018–2019. The long-term record of the mixed layer depths shows no significant change; thus, the uplift of nutrients during winter mixing cannot support the trend and variations of the integrated Chl.a. Additional biological parameters of specific pico-phytoplankton populations and integrated bacterial production and abundance were measured in 2013–2021, but the measurements were too sparse to follow a clear interannual dynamics. Yet significantly higher average levels for integrated primary production and bacterial abundances were observed during the anticyclonic period (as for Chl.a). The combined impacts of the BiOS mechanism and global warming, and hence the increase in LIW residence time and buoyancy, may impact the primary producers’ biomass at the photic zone. This latter feedback may slightly counter the enhanced oligotrophication due to enhanced stratification.